Predictors of prolonged stay in patients with community‐acquired pneumonia and complicated parapneumonic effusion. Issue 1 (29th October 2015) - Kim, Junghyun; Park, Jong Sun; Cho, Young‐Jae; Yoon, Ho Il; Lee, Jae Ho; Lee, Choon‐Taek; Lim, Hyo‐Jeong; Kim, Deog Kyeom
Abstract: Background and objective: Development of CPE in CAP is associated with prolonged hospital stay and it may increase the morbidity and mortality. We aimed to identify microbiological and clinical factors that predicate a prolonged hospital admission in patients treated with a tube thoracostomy to control CPE. Methods: This retrospective cohort included patients with CPE requiring chest tube drainage in a tertiary referral Korean hospital from 1 January 2004 to 30 July 2012. After dichotomous grouping according to the mean duration of hospital stay, clinical, laboratory and microbiological parameters were compared. Results: The final analysis included 158 patients with CPE. The majority were male (130, 85.0%), and the mean age was 62.8 years. The mean duration of hospital stay was 17.7 (±10.2) days. The mean duration of chest tube drainage was 9.6 (±6.7) days. Streptococcus viridans (48.4%) was the most common pathogen. Intrapleural fibrinolysis was performed in 85 (53.8%); additional tube insertion was needed in 40 (25.3%) patients. In the multivariate analysis after adjusting for covariates, a prolonged hospital stay was associated with fever (aOR: 3.42, P = 0.02), lower PaO2 (aOR: 4.89, P = 0.007) and haemoglobin (aOR: 4.90, P = 0.003) levels, and an increased blood neutrophil fraction (aOR: 3.83, P = 0.01) on admission as well as the identification of microbes in CPE (aOR: 4.14, P = 0.03), and ineffective pleural drainage (aOR: 3.28, P = 0.03). Conclusions: This study suggests that physicians should note the clinical symptoms and laboratory findings of severe infection and effectiveness of pleural drainage to predicate which patients with a CAP needing thoracostomy for CPE will have a prolonged hospital stay. Abstract : This study was aimed to find the association between clinical, laboratory, microbiologic findings and hospital stay in patients with CPE. Clinical symptoms, effectiveness of pleural drainage and laboratory findings represented severe infection rather than chemistry profiling of CPE when managing patients with a tube thoracostomy for CPE.